2017
DOI: 10.1002/ctpp.201700143
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous effect of an external magnetic field and gas‐induced friction on the caging of particles in two‐dimensional Yukawa systems

Abstract: We investigate the simultaneous effect of a static homogeneous external magnetic field and a background gas medium on the quasi‐localization of the dust particles—characterized quantitatively by cage correlation functions—in strongly coupled two‐dimensional Yukawa systems. We apply the Langevin dynamics computer simulation method in which the frictional and Lorentz forces are taken into account. Both the presence of the magnetic field and the friction originating from the background gas, when acting alone, inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The magnetic field results in this by forcing the particles to move on circular trajectories. When the Larmor radius is smaller than the interparticle separation, diffusive motion across the field lines is significantly hindered, and the caging time is enlarged [24]. The effect of friction on the caging time is similar [25] but results from a different physical mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic field results in this by forcing the particles to move on circular trajectories. When the Larmor radius is smaller than the interparticle separation, diffusive motion across the field lines is significantly hindered, and the caging time is enlarged [24]. The effect of friction on the caging time is similar [25] but results from a different physical mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The duration of the localization can be quantified by means of the so-called "cage correlation functions". The effect of a static uniform external magnetic field on the cage correlation functions in frictionless two-dimensional Yukawa systems has been investigated by Dzhumagulova et al, [24] while the effect of the friction force, induced by the presence of the buffer gas, has been addressed by Dzhumagulova et al [25] Here, our aim is to study the simultaneous effect of the magnetic field and the friction on the cage correlation functions. The interplay of these two effects is an open question that can only be answered by a systematic parametric study due to the inherent non-linearity of the system under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Our present study is motivated by the recent results obtained in an investigation of the simultaneous effect of an external magnetic field and gas‐induced friction on the caging of particles, which is termed as quasi‐localization of the particles in these systems . It was shown that although the magnetic field and the friction, when acting alone, increase the caging time, when they are present simultaneously, their effects combine in a non‐trivial manner and act against each other within some region of the parameter values.…”
Section: Introductionmentioning
confidence: 96%
“…It was already applied in ref. and is also used for the present simulations. The feature of this numerical scheme is an independence of the time step from the magnetic field strength .…”
Section: Introductionmentioning
confidence: 99%